PEMBUATAN GAME AUGMENTED REALITY FIRST PERSON SHOOTER "APOCALYPTIC REALITY" DENGAN VUFORIA - Dwiky Anderson; Jeanny Pragantha; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
"Apocalyptic Reality" is a first-person shooter game that can be played on Android device. Augmented reality features make a three-dimensional display. This game is made using the Unity3D game engine and the Vuforia software development kit to detect the position and rotation of the device in the real world. There are nine stages available in this game. player must collect money to buy items in the Shop and fight zombies that arrives. The game was tested using black box testing, alpha testing, and beta testing with questionnaire to 30 respondents. The test results show that this game has provide a unique way to play First Person Shooter and this game can be played using minimal Android Version 5 or above.